IMPLEMENTASI METODE RESITASI SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Kurniawan Yudianto (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2022)
The recitation method, namely the recitation method or assignment assignment is one of the teaching methods that can be chosen by educators, which in practice, educators demand that students play an active role in teaching and learning activities so that they are able to complete the tasks given by educators to do outside lesson hours. The assignments given are usually individual, but can also be given in groups. The focus of the problem in this research are: (1) How is the implementation of the assignment method (recitation) at Madrasah Ibtidaiyah Al Asy'ariyah Banjarsari Bandarkedungmulyo Jombang?, (2) How are student learning outcomes using the assignment method (recitation) at Madrasah Ibtidaiyah Al Asy'ariyah Banjarsari Bandarkedungmulyo Jombang?. The research in this thesis uses classroom action research (CAR) research which is carried out collaboratively. The data collection technique used is the test and observation technique (observation). The results of this study indicate that: (1) The first step in planning this action is to analyze the components and content of the items, determine the learning materials, examine the class III mathematics textbooks, develop a syllabus, develop a lesson plan, and make student activity sheets. The implementation process in the first cycle, the researcher succeeded in explaining to students about doing multiplication which resulted in three-digit numbers and division of three-digit numbers and learning by saying and doing would obtain high absorption of learning outcomes. The evaluation process is carried out at each meeting after the learning process takes place to determine how far the development of the method being developed has been successful as planned. (2) The results of class III Mathematics learning by applying the assignment method (recitation) are classified as very good. The results of this study can be seen from the average pre-test and post-test where the pre-test score is 76.19% while the Post-Test reaches a value of 95.23%, there is a very good increase.